PERTUNJUKAN OPERA AGNUS PERDITUS KARYA MATHEUS WASI BANTOLO - Estherlita Priskanike Yudiaernanda; Supriyanto Supriyanto (Greget, 2021)
Agnus Perditus is a dance genre opera, Agnus Perditus is taken from Latin means lost sheep. The work of Agnus Perditus was directed by Matheus Wasi Bantolo for a joint Christmas event between the Indonesian Institute of the Arts Surakarta and Sebelas Maret University which was held at Teater Besar of the Indonesian Art Institute, Surakarta. In 2016 the combined Christmas was directed by Matheus Wasi Bantolo. The theoretical basis in this study uses the concept of working on Rahayu Supanggah which examines the process of working on an art, as well as the theory of form approach from Suzanne K. Langer in her book entitled "Problematic Art" which is translated by F.X Widaryanto. This research is a qualitative research with analytical descriptive method, which describes the results of the observations clearly based on the actual situation. The data collection stage was carried out through observation, interviews, and literature study. The purpose of this research is to reveal the form of the work of Matheus Wasi Bantolo's Agnus Perditus. Opera Agnus Perditus was presented in a joint Christmas celebration event between the Indonesian Institute of the Arts Surakarta and the Sebelas Maret University Surakarta. The work is inspired by the New Testament Bible story in the Gospel of Luke 15: 11-32, which tells of a lost sheep and the film "Prodigal Son" which tells of a lost sheep or a lost child has been found, so it is used as an idea to work on creation the work of Agnus Perditus.Keywords: Dance form, working process, opera, Matheus Wasi Bantolo.